Ion selective membrane, sodium ion sensor and preparation method of sodium ion sensor

By designing the glass transition temperature of polymer polymer and adding ester-philic plasticizing groups, the problem of decreased sensitivity caused by plasticizer loss in ion selective electrodes is solved, and a more stable and sensitive sodium ion sensor is achieved.

CN119574671APending Publication Date: 2025-03-07SICHUAN XINCHENG BIOLOGICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738065.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In existing ion selective electrodes, the slow loss of plasticizer leads to a decrease in sensor sensitivity.

Method used

By designing the glass transition temperature of the polymer polymer is less than or equal to 0°C, and adding ester-philic plasticizing groups to the polymer polymer, the dependence on plasticizers is reduced and the flexibility and stability of the film is improved.

Benefits of technology

It solves the problem of sensitivity reduction caused by plasticizer loss, improves the stability and sensitivity of the sodium ion sensor, and extends the service life of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574671A_ABST
    Figure CN119574671A_ABST
Patent Text Reader

Abstract

The invention discloses an ion selective membrane, a sodium ion sensor and a preparation method of the ion selective membrane. The ion selective membrane comprises the following components in percentage by mass: 90-95% of a high-molecular polymer, 0.5-1.5% of an ion exchanger and 4.5-8.5% of an ion carrier, the high-molecular polymer contains lipophilic plasticizing groups, and the glass transition temperature of the high-molecular polymer is less than or equal to 0 DEG C. The sodion sensor comprises a sodion working electrode and a reference electrode, the sodion working electrode is sequentially coated with Ag / AgCl slurry, carbon slurry and an ion selective membrane, the Ag / AgCl slurry is coated on an Au substrate of the PCB, and the ion selective membrane is the ion selective membrane. The ion selective membrane and the sodium ion sensor do not depend on plasticizers, and the sensitivity stability of the sensor in long-term use is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical sensors, and in particular to an ion selective membrane, a sodium ion sensor and a preparation method thereof. Background Art

[0002] Sodium ion sensors are widely used in medicine, biochemistry, pharmaceuticals, chemicals, environmental protection, food and many other fields.

[0003] Ion selective electrodes (ISE) are usually composed of ion selective membranes, internal electrolyte solutions, and internal reference electrodes. In recent years, the emerging solid-state ion selective electrodes replace the internal electrolyte solution with solid carbon slurry. The current ion selective membranes are usually made of polymer materials (such as PVC, carboxylated PVC, silicone rubber RTV3140, polyurethane, etc.), plasticizers, ion salts, and carriers. Since ion selective electrodes must be used at room temperature, plasticizers must be added to ensure that the membrane is flexible, but plasticizers will slowly drain from the membrane, causing changes in the membrane and causing the sensitivity of the sensor to slowly decrease.

[0004] In view of this, this patent application is filed. Summary of the invention

[0005] In order to solve the technical problem of decreased sensor sensitivity caused by slow loss of plasticizer in the ion selective membrane of the current ion selective electrode, the present invention provides an ion selective membrane for a sodium ion sensor, and also provides a sodium ion sensor and a preparation method thereof.

[0006] The present invention is achieved through the following technical solutions: The first object of the present invention is to provide an ion selective membrane for a sodium ion sensor, comprising the following components in mass percentage: 90% to 95% of a high molecular polymer, 0.5% to 1.5% of an ion exchanger, and 4.5% to 8.5% of an ion carrier; The high molecular polymer has an lipophilic plasticizing group, and the glass transition temperature of the high molecular polymer is less than or equal to 0°C.

[0007] Since the plasticizer in the current ion selective membrane will slowly drain from the membrane, in order to solve this problem, the present invention considers removing the plasticizer from the ion selective membrane, and seeks a suitable polymer. The inventor finds that when the glass transition temperature of the polymer is less than or equal to 0°C, the polymer can be guaranteed to have suitable flexibility. Furthermore, in order to meet the requirements of room temperature use, storage and transportation, the inventor designs the glass transition temperature of the polymer to ≤0°C. At the same time, it is also invented that when the polymer has a lipophilic plasticizing group, a sufficiently low glass transition temperature can be provided. On the other hand, the polymer with a lipophilic plasticizing group can be better compatible with ionic salts and carriers and evenly distributed in the solvent.

[0008] In the present invention, by improving the performance of the polymer material itself, it no longer relies on the flexibility of the plasticizer itself. Compared with the current practice of adding plasticizers, there is no need to consider the loss of plasticizers. This technical solution solves the technical difficulty of the slow decrease in sensitivity caused by the loss of plasticizers in existing sodium ion sensors.

[0009] In an optional embodiment, the glass transition temperature of the high molecular polymer is -10° C. to -75° C. The inventors have found that the high molecular polymer at this glass transition temperature has better flexibility and can also ensure good compatibility with ionic salts and carriers.

[0010] In an optional embodiment, the main chain of the high molecular polymer is a rigid main chain; Preferably, the high molecular polymer is any one of dodecyl acrylate, dodecyl methacrylate, isooctyl acrylate, caprolactone acrylate, and isodecyl acrylate.

[0011] The inventors further studied and found that the polymer also needs to have appropriate plasticity, combined with flexibility, and the main chain of the polymer is designed to have appropriate rigidity. Any one of dodecyl acrylate, dodecyl methacrylate, isooctyl acrylate, caprolactone acrylate, and isodecyl acrylate can be selected, and isodecyl acrylate is more preferably selected.

[0012] In an optional embodiment, the ion exchanger is a fat-soluble ion salt, and the ion carrier is fat-soluble, so as to be better compatible with high molecular polymers and have better performance.

[0013] The second object of the present invention is to provide a sodium ion sensor, comprising a sodium ion working electrode and a reference electrode, wherein the sodium ion working electrode is coated with Ag / AgCl slurry, carbon slurry, and an ion selective membrane in sequence, wherein the Ag / AgCl slurry is coated on an Au substrate of a PCB, and the ion selective membrane adopts the ion selective membrane as described in any one of the above items; And / or, the thickness of the Ag / AgCl slurry and the carbon slurry coated on the sodium ion working electrode is 15-25 μm, and the thickness of the coated ion selective membrane is 25-50 μm.

[0014] In an optional embodiment, a redox substance accounting for 2% to 5% by mass is added to the carbon slurry of the sodium ion working electrode, and the redox substance is any one of graphene, carbon nanotubes, polyaniline, polypyrrole, and polythiophene.

[0015] Due to the emerging solid-state ion selective electrodes in recent years, the use of solid carbon slurry instead of traditional internal electrolyte solution can extend the life of the electrode, but there is also a problem of long adjustment time. In order to solve this technical difficulty, the present invention adopts a method of adding redox substances to the carbon slurry, which can accelerate the conversion speed of the electrical signal, thereby shortening the start-up time of the electrode. Preferably, polyaniline is used.

[0016] In an optional embodiment, the reference electrode is coated with Ag / AgCl paste, carbon paste, and polymer film in sequence, the Ag / AgCl paste is coated on the Au substrate of the PCB, 2.0% to 4.0% of redox substance is added to the carbon paste of the reference electrode, and the redox substance is any one of graphene, carbon nanotubes, polyaniline, polypyrrole, and polythiophene; And / or, the polymer film is isodecyl acrylate; And / or, the thickness of the Ag / AgCl slurry and the carbon slurry coated on the reference electrode is 15-25 μm, and the thickness of the coated polymer film is 25-50 μm.

[0017] The reference electrode also has the problem of long carbon paste adjustment time. Using the same method, the present invention also adds redox substances to the carbon paste of the reference electrode to shorten the start-up time of the electrode.

[0018] At the same time, compared with the existing reference electrode, the present invention also designs a reference electrode with a three-layer structure of Ag / AgCl slurry, carbon slurry, and polymer film. Such a design is conducive to forming a more stable potential as a reference electrode.

[0019] In an optional embodiment, in the Ag / AgCl slurry of the reference electrode, silver is first plated on the PCB by electroplating, and then an Ag / AgCl complex is formed by an electrochemical reaction.

[0020] At present, the reference electrode of the ion sensor mostly adopts Ag / AgCl slurry to provide a stable potential, and the reference solution mostly adopts a saturated KCl solution. The Ag / AgCl slurry is attached to the PCB by dispensing. However, the problem is that the Ag / AgCl slurry is easily foamed by the saturated KCl solution, resulting in unstable potential, which leads to inaccurate test results. In order to solve this problem, the present invention adopts an electroplating method to plate silver on the PCB, and then forms an Ag / AgCl complex through an electrochemical reaction. Due to the electroplating method, the Ag / AgCl complex can be firmly attached to the PCB for a long time, avoiding the unstable potential caused by foaming.

[0021] The third object of the present invention is to provide a method for preparing the sodium ion sensor described in any one of the above items, comprising: Preparation of sodium ion working electrode: On the Au substrate of PCB, first coat Ag / AgCl slurry, dry it, then coat it with carbon slurry, and then coat it with ion selective membrane after drying; The ion selective membrane is made of high molecular polymer, ion exchanger and ion carrier dissolved in tetrahydrofuran; The reference electrode was prepared by coating Ag / AgCl slurry on the Au substrate of PCB, drying it, then coating it with carbon slurry, and then drying it, then coating it with a polymer film, and using tetrahydrofuran to dissolve the polymer film.

[0022] In an optional embodiment, the preparation process of the Ag / AgCl slurry of the reference electrode is: First, a layer of silver is plated on the PCB, and then the silver coating is immersed in nitric acid for 20-30 seconds to activate it. The activated silver coating is then immersed in (NH4)2S solution and FeCl3 solution for 20-30 seconds each for chlorination. The immersion temperature is 40-80°C. Then, it is immersed in 0.1-0.3moL / L hydrochloric acid, and a voltage of 1~2V is applied to form an Ag / AgCl complex through an anodic reaction. Finally, it is removed and washed twice with water, and dried at 100°C for 15min.

[0023] In the present invention, the Ag / AgCl composite formed by the preparation of the reference electrode Ag / AgCl slurry has long-lasting durability in aqueous solution and can maintain a stable potential for a long time, and there will be no problem of potential instability caused by the Ag / AgCl slurry being foamed like glue dispensing.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The ion selective membrane provided by the present invention designs the glass transition temperature of the polymer to ≤0°C. At the same time, it is also invented that when the polymer has a lipophilic plasticizing group, a sufficiently low glass transition temperature can be provided. On the other hand, the polymer with the lipophilic plasticizing group can be better compatible with ionic salts and carriers and evenly distributed in the solvent. Therefore, by improving the performance of the polymer material itself, it is no longer dependent on the flexibility of the plasticizer itself, and there is no need to consider the loss of the plasticizer.

[0025] 2. The main chain of the high molecular polymer in the ion selective membrane design provided by the present invention is rigid, thus ensuring the good performance of the ion selective membrane.

[0026] 3. In a sodium ion sensor provided by the present invention, redox substances such as polyaniline are added to the carbon pastes of the working electrode and the reference electrode, which can accelerate the conversion speed of the electrical signal and shorten the start-up time of the electrode.

[0027] 4. The sodium ion sensor provided by the present invention improves the preparation method of the Ag / AgCl slurry on the reference electrode, and the silver layer is plated on the PCB by electroplating. The Ag / AgCl complex can be firmly attached to the PCB for a long time, avoiding the potential instability caused by bubbling. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The sensitivity stability diagrams are obtained by testing three gradient aqueous solution samples using the sodium ion sensors obtained in Example 1 and Comparative Example 1 respectively.

[0029] Figure 2 It is a comparison chart of the potential stability test of the reference electrode of Example 1, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0031] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially. and (b), and may also include steps (b) and (a) performed sequentially. For example, the method may further include step (c), means that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), It may also include steps (a), (c) and (b), or it may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] In order to solve the problem of plasticizer loss in the current ion selective membrane, the present invention provides a sodium ion working electrode solution, which is a three-layer structure consisting of Ag / AgCl slurry, carbon slurry, and ion selective membrane. The silver slurry is a common commercially available silver slurry, such as DuPont 5874, Sun Chemical C2130809D5, etc.; the carbon slurry is a common commercially available carbon slurry, such as Japan Jujo CH-8, with 2.0%-4.0% of polyaniline (Tianjin Xiensi, product number: E-0239067) added by mass ratio; the ion selective membrane is made of high molecular polymer (90%-95%, w / w), ion exchanger (0.5%-1.5%, w / w), and ion carrier (4.5%-8.5%, w / w). The high molecular polymer is isodecyl acrylate (Sartomer, product number SR395NS), the ion exchanger is potassium tetrakis (4-chlorophenyl) borate (Aladdin, product number P160343), and the ion carrier is sodium ion carrier III (ETH2120, Sigma, product number 71734).

[0037] The present invention provides a reference electrode scheme, which is a three-layer structure consisting of Ag / AgCl paste, carbon paste, and polymer film. The silver paste is common commercially available silver paste, such as DuPont 5874, Sun Chemical C2130809D5, etc. The carbon paste is common commercially available carbon paste, such as Japan Jujo CH-8. Polyaniline (Tianjin Xiensi, product number: E-0239067) with a mass ratio of 2.0%-4.0% is added to the carbon paste. The polymer film is made of a polymer material (100%, w / w), and the polymer material is isodecyl acrylate (Sartomer, product number SR395NS). The preparation method of Ag / AgCl slurry has also been improved. A layer of silver of about 5-8 μm is plated on the PCB using a silver plating process, and then the silver plating layer is activated using acid. The specific method is to immerse the silver plating layer in dilute nitric acid with a volume ratio of 5% for 20-30 seconds to make the silver plating layer bright and clean, and then chlorinate the surface of the silver plating layer to convert it into a silver / silver chloride electrode. The specific method is to immerse the activated PCB electrode silver plating layer in (NH4)2S solution and FeCl3 solution for 20-30 seconds each, the immersion temperature is 40-80°C, and then immersed in 0.1-0.3moL / L hydrochloric acid, apply a voltage of one to two volts, and form an Ag / AgCl complex through an anode reaction. Finally, it is fished out and washed twice with water, and dried at 100°C for 15 minutes.

[0038] The following is an explanation through specific examples.

[0039] Implementation Case 1: A sodium ion sensor, the preparation method is as follows: (1) Preparation of sodium ion working electrode: On the Au substrate of the PCB, a 15-25μm thick Ag / AgCl paste is coated, and after drying at 120℃ for 20min, a 15-25μm thick carbon paste is coated. The carbon paste uses Japanese CH-8, and 2.0% polyaniline is added to the carbon paste. After drying at 130℃ for 30min, a 25-50μm ion selective membrane is coated.

[0040] The ion selective membrane uses isodecyl acrylate (95%, w / w), potassium tetrakis(4-chlorophenyl)borate (0.8%, w / w), and sodium ion carrier III (4.2%, w / w) as raw materials, and these four raw materials are dissolved in 1.2g of tetrahydrofuran and stirred evenly.

[0041] (2) Reference electrode preparation: On the Au substrate of the PCB, apply a 15-25μm thick Ag / AgCl slurry, dry it at 120℃ for 20min, then apply a 15-25μm thick carbon slurry. The carbon slurry uses Japanese CH-8 and adds 2.0% polyaniline. After drying at 130℃ for 30min, apply a 25-50μm isodecyl acrylate polymer film. Use 1.2g of tetrahydrofuran to dissolve 0.80g of the polymer material.

[0042] The preparation method of Ag / AgCl slurry is as follows: A layer of silver of about 5-8μm is plated on the PCB using the silver plating process, and then the silver plating layer is immersed in 5% dilute nitric acid by volume for 20-30 seconds to make the silver plating layer bright and clean. Then the activated PCB electrode silver plating layer is immersed in (NH4)2S solution and FeCl3 solution for 20-30 seconds each, and the immersion temperature is 40-80℃, and then immersed in 0.1-0.3moL / L hydrochloric acid, and a voltage of one to two volts is applied to form an Ag / AgCl complex through the anode reaction. Finally, it is removed and washed twice with water and dried at 100℃ for 15min.

[0043] Comparative Example 1: The difference between this comparative example and Example 1 is the components of the ion selective membrane, specifically, the components of the ion selective membrane are di(2-ethylhexyl) sebacate (63%, w / w), potassium tetrakis(4-chlorophenyl)borate (4%, w / w), sodium ion carrier III (1%, w / w), carboxylated PVC (32%, w / w), and these four raw materials are dissolved in 1.2g of tetrahydrofuran and stirred evenly. The rest is the same as Example 1.

[0044] Comparative Example 2: The difference between this comparative example and Example 1 is the preparation of the reference electrode: On the Au substrate of the PCB, a 15-25 μm thick Ag / AgCl slurry is coated, and then a 15-25 μm thick carbon slurry is coated after drying at 120° C. for 20 min. The carbon slurry is Japanese CH-8, and then a 25-50 μm isodecyl acrylate polymer film is coated after drying at 130° C. for 30 min. 1.2 g of tetrahydrofuran is used to dissolve 0.80 g of the polymer material. The rest is the same as in Example 1.

[0045] Comparative Example 3: The difference between this comparative example and Example 1 lies in the preparation of the reference electrode: On the Au substrate of the PCB, a 15-25 μm thick Ag / AgCl slurry was coated and dried at 120° C. for 20 min. The conventional dispensing method was adopted. The rest was the same as in Example 1.

[0046] test: 1. The sodium ion sensor obtained in Example 1 and Comparative Example 1 was used to test three gradient aqueous solution samples (sodium ion concentrations were 98mmol / L, 142mmol / L, and 180mmol / L, respectively). The results are as follows: Figure 1 As shown in Figure 1 It can be seen that the sensitivity stability of the sensor of the present invention is significantly better than that of the comparative example 1 as the measurement time increases. The stability of the sodium ion sensor in the comparative example 1 gradually decreases due to the gradual loss of plasticizer, and its sensitivity decreases by about 1 unit. However, the sensitivity stability of the sensor of the present invention remains at a high level over time, and its sensitivity can remain stable within 30 days.

[0047] 2. The inventor further studied the potential stability of the reference electrode. The research process is as follows: the reference electrode scheme is implemented on the PCB as the working electrode, the commercial Ag / AgCl electrode is used as the reference electrode, and the saturated KCl solution is used as the electrolyte solution. The potential stability of the working electrode (i.e. the invented reference electrode) is continuously tested. The results are shown in Figure 2 shown.

[0048] Depend on Figure 2 It can be seen that the potential of the reference electrode of the present invention can quickly reach a stable state within about 30 minutes, while the conventional one needs about 90 minutes to reach a stable state.

[0049] Using the same method, the inventors studied the potential stability of reference electrodes prepared by conventional dispensing and electroplating. Figure 2 As shown in . Figure 2 It can be seen that the potential of the reference electrode prepared by the method of Example 1 is always in a stable state, while the potential of the reference electrode obtained in Comparative Example 3 drops sharply after being used for about 52 hours.

[0050] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An ion selective membrane for a sodium ion sensor, characterized in that: The invention comprises the following components in the following mass percentages: 90% to 95% of high molecular polymer, 0.5% to 1.5% of ion exchanger, and 4.5% to 8.5% of ion carrier; The high molecular polymer has an lipophilic plasticizing group, and the glass transition temperature of the high molecular polymer is less than or equal to 0°C.

2. The ion selective membrane for sodium ion sensor according to claim 1, characterized in that: The glass transition temperature of the high molecular polymer is -10°C to -75°C.

3. An ion selective membrane for a sodium ion sensor according to claim 1 or 2, characterized in that: The main chain of the high molecular polymer is a rigid main chain; Preferably, the high molecular polymer is any one of dodecyl acrylate, dodecyl methacrylate, isooctyl acrylate, caprolactone acrylate, and isodecyl acrylate.

4. An ion selective membrane for a sodium ion sensor according to claim 1 or 2, characterized in that: The ion exchanger is a fat-soluble ion salt, and the ion carrier is fat-soluble.

5. A sodium ion sensor, characterized in that: It comprises a sodium ion working electrode and a reference electrode, wherein the sodium ion working electrode is coated with Ag / AgCl slurry, carbon slurry, and an ion selective membrane in sequence, wherein the Ag / AgCl slurry is coated on an Au substrate of a PCB, and the ion selective membrane is the ion selective membrane according to any one of claims 1 to 4; And / or, the thickness of the Ag / AgCl slurry and the carbon slurry coated on the sodium ion working electrode is 15-25 μm, and the thickness of the coated ion selective membrane is 25-50 μm.

6. A sodium ion sensor according to claim 5, characterized in that: The carbon slurry of the sodium ion working electrode is added with a redox substance accounting for 2.0%-4.0% of the mass fraction thereof, and the redox substance is any one of graphene, carbon nanotubes, polyaniline, polypyrrole and polythiophene.

7. A sodium ion sensor according to claim 5, characterized in that: The reference electrode is coated with Ag / AgCl slurry, carbon slurry, and polymer film in sequence, the Ag / AgCl slurry is coated on the Au substrate of the PCB, 2.0%-4.0% of redox material is added to the carbon slurry of the reference electrode, and the redox material is any one of graphene, carbon nanotubes, polyaniline, polypyrrole, and polythiophene; And / or, the polymer film is isodecyl acrylate; And / or, the thickness of the Ag / AgCl slurry and the carbon slurry coated on the reference electrode is 15-25 μm, and the thickness of the coated polymer film is 25-50 μm.

8. A sodium ion sensor according to claim 7, characterized in that: In the Ag / AgCl slurry of the reference electrode, silver is first plated on the PCB by electroplating, and then an Ag / AgCl complex is formed by electrochemical reaction.

9. The method for preparing a sodium ion sensor according to any one of claims 5 to 8, characterized in that: include: Preparation of sodium ion working electrode: On the Au substrate of PCB, firstly coat Ag / AgCl slurry, dry it, then coat it with carbon slurry, and then coat it with ion selective membrane after drying; The ion selective membrane is made of high molecular polymer, ion exchanger and ion carrier dissolved in tetrahydrofuran; The reference electrode was prepared by coating Ag / AgCl slurry on the Au substrate of PCB, drying it, then coating it with carbon slurry, and then drying it, then coating it with a polymer film, and using tetrahydrofuran to dissolve the polymer film.

10. The method for preparing a sodium ion sensor according to claim 9, characterized in that: The preparation process of the Ag / AgCl slurry of the reference electrode is as follows: First, a layer of silver is plated on the PCB, and then the silver coating is immersed in nitric acid for 20-30 seconds to activate it. The activated silver coating is then immersed in (NH4)2S solution and FeCl3 solution for 20-30 seconds each for chlorination. The immersion temperature is 40-80°C, and then it is immersed in 0.1-0.3moL / L hydrochloric acid. A voltage of 1-2V is applied to form an Ag / AgCl complex through an anodic reaction. Finally, it is removed and washed twice with water and dried at 100°C for 15 minutes.